2010
DOI: 10.1111/j.1365-2036.2010.04301.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: the role of self‐expanding plastic stents for benign oesophageal strictures

Abstract: SUMMARY BackgroundTreatment of refractory or recurrent benign oesophageal strictures is demanding and surgery may be the only available option. The role of self-expanding plastic stents (SEPS) in the treatment of these strictures is still controversial because of the conflicting results of various studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 26 publications
3
53
0
1
Order By: Relevance
“…9 Recent reports have also tempered the initial enthusiasm regarding the use of SEPSs in the management of RBESs. 19 A retrospective case series of 30 patients who underwent SEPS placement for benign esophageal disorders reported a high rate (62.1%) of stent migration with a disappointingly low rate (17%) of long-term improvement after stent removal. 16 In addition, repeat stenting was required in 55% of the patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…9 Recent reports have also tempered the initial enthusiasm regarding the use of SEPSs in the management of RBESs. 19 A retrospective case series of 30 patients who underwent SEPS placement for benign esophageal disorders reported a high rate (62.1%) of stent migration with a disappointingly low rate (17%) of long-term improvement after stent removal. 16 In addition, repeat stenting was required in 55% of the patients.…”
Section: Discussionmentioning
confidence: 97%
“…However, data on the efficacy of these stents in RBES patients are mixed, and a relatively high rate of stent migration has been reported. [13][14][15][16][17][18][19] Moreover, an unexpectedly high rate of SEPS-related complications has also been reported in some series. 19 Biodegradable stents have recently been developed.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The surgery employed did not altered the results, and the individualized indication was made for each case, depending on the stenosis level, previous surgeries and patient conditions. In refractory or recurrent cases, an option recommended by some authors is the use of self-expanding stents 17,18,24 . Pinotti et al 21 reported 12 cases of this serious complication of esophageal lesions, from which eight were probed in the postoperative stage of different types of abdominal interventions and four due to clinical diseases.…”
mentioning
confidence: 99%
“…Others authors proposed a proximal fixation of the stent on the esophageal mucosa by a clip to prevent stent migration [57]. Delayed migration could be, at least in some cases, the inevitable consequence of the dilating efficacy of the plastic stents [58]. Dysphagia is generally improved rapidly but long-term efficacy is small (between 6 to 40% at 1 year) especially for anastomotic strictures [59].…”
Section: Complicationsmentioning
confidence: 98%